2019
DOI: 10.1051/matecconf/201929602004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Characterizing Mechanical Damage in Packaged Bananas in the Post-harvest Supply Chain

Abstract: Quality deterioration in packaged bananas caused by mechanical damage along the post-harvest supply chains (SC) remains obscure until the packages are unpacked for sale at the retail stores and therefore, the mechanism of damage occurrence remains unclear. This study assessed the mechanical damage levels of bananas in 300 cartons from pack houses to retail stores in Australia. The damage across the SC were shown to be progressive across the SC. Bruising and neck damage levels in bananas increased from the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The authors suggested the placement of force-absorbing material at the bottom of the carton as an economical way to reduce damage incurred by the fruit. Fernando et al [117] showed that impact load caused severe neck injuries in packed bananas, which became worse with increasing height. Contrary to the reports by Lu et al [115] and Fadiji et al [116], the highest neck injuries, approximately 94% and 91% at heights 30 cm and 50 cm, respectively, were concentrated on bananas in the top two layers inside the carton.…”
Section: Impact Strengthmentioning
confidence: 99%
“…The authors suggested the placement of force-absorbing material at the bottom of the carton as an economical way to reduce damage incurred by the fruit. Fernando et al [117] showed that impact load caused severe neck injuries in packed bananas, which became worse with increasing height. Contrary to the reports by Lu et al [115] and Fadiji et al [116], the highest neck injuries, approximately 94% and 91% at heights 30 cm and 50 cm, respectively, were concentrated on bananas in the top two layers inside the carton.…”
Section: Impact Strengthmentioning
confidence: 99%
“…Avoiding mechanical damages is a problem that must be paid attention to in the procedure of banana transportation. In the procedure of banana transportation, apart from improving the transportation efficiency and reducing the labor intensity, the probability of mechanical damages to the bananas should be minimized as much as possible [29][30][31][32]. The most primitive method of transportation was to pick banana bunches by human shoulders, which is convenient and flexible to operate but requires high physical ability of workers.…”
Section: Banana Transportationmentioning
confidence: 99%